2017
DOI: 10.1021/acs.jpcc.7b02896
|View full text |Cite
|
Sign up to set email alerts
|

Iodine versus Bromine Functionalization for Bottom-Up Graphene Nanoribbon Growth: Role of Diffusion

Abstract: Deterministic bottom-up approaches for synthesizing atomically well-defined graphene nanoribbons (GNRs) largely rely on the surface-catalyzed activation of selected labile bonds in a molecular precursor followed by step growth polymerization and cyclodehydrogenation. While the majority of successful GNR precursors rely on the homolytic cleavage of thermally labile CBr bonds, the introduction of weaker C-I bonds provides access to monomers that can be polymerized at significantly lower temperatures, thus helpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 58 publications
(155 reference statements)
4
42
1
Order By: Relevance
“…The doped chGNRs, as the pristine ones, display preferential orientations on the substrate, but notably shorter than pristine chGNRs [21,24], reaching lengths of up to 15 nm. We speculate that the attachment of NH 2 groups lowers the diffusion of precursors and thus hinders their polymerization processes [44]. The edges of the resulting NH 2 -chGNRs are quite inhomogeneous, and their width is larger than pristine chGNRs, suggesting the presence of a certain amount of NH 2 groups attached to the edges (see Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
“…The doped chGNRs, as the pristine ones, display preferential orientations on the substrate, but notably shorter than pristine chGNRs [21,24], reaching lengths of up to 15 nm. We speculate that the attachment of NH 2 groups lowers the diffusion of precursors and thus hinders their polymerization processes [44]. The edges of the resulting NH 2 -chGNRs are quite inhomogeneous, and their width is larger than pristine chGNRs, suggesting the presence of a certain amount of NH 2 groups attached to the edges (see Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
“…The critical role of diffusion for the formation of GNRs was recently demonstrated by C. Bronner et al . in their study of iodine- and bromine- containing molecules on the Au(111) surface 38 . It was shown that even though dehalogenation of iodinated monomers occurs on gold at lower temperature, the surface-stabilized monomers do not start polymerisation right away due to their reduced diffusivity.…”
Section: Discussionmentioning
confidence: 99%
“…Being part of a multistep process, the Ullmann-type reaction between specifically designed molecules is aimed to result in the formation of polymerized molecular chains, which can be transformed to atomically precise graphene nanoribbons upon further cyclodehydrogenation at higher temperatures 7 , 15 . In the majority of the studies this method was used for the preparation of GNRs with various atomic structures on Au(111), Au(110) or Au(788) substrates 7 , 15 29 , 38 . In particular, the most widely studied nanoribbon is that with armchair edges and a width (N) of seven carbon atoms (7-AGNR) that grows from the 10,10′-dibromo-9,9′-bianthracene (DBBA) 15 20 , 23 , 25 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…By functionalizing one of those groups or a combination thereof can implement heteroatom‐doped GNRs, phenyl‐modified CGNRs, and so forth. Besides, iodinated precursors instead of the brominated ones can also be applied to form GNRs . Therefore, the DBTT‐typed precursors play an important role in the preparation of pristine, doped CGNRs, and even heterojunctions.…”
Section: Crucial Elements and Growth Procedures Of Gnrsmentioning
confidence: 99%